Operation Pedro Pan : the untold exodus of 14,048 Cuban children - Conde, Yvonne M. (Routledge, 2000)
This book investigates the events and key figures surrounding the exodus, including the roles of the Catholic Church and the State Department, and the extent of the CIA's involvement.